Jargon Used by Balinese Traditional Weaving Community - Pandita, Sang Putu Ari; Ramendra, Dewa Putu; Mahendrayana, Gede (Universitas Pendidikan Ganesha, 2021)
This research was conducted in order to find out the jargons that exist in Balinese traditional weaving community. This research was designed in the form of descriptive qualitative study. The method used in this study were conducting observation and interview. Observation was done in order to observe the condition and jargons used in the weaving process. Meanwhile, interview was done by interviewing three informants and the purpose of the interview was to find out all of the jargons used in this community. The results showed that there were forty-one jargons found in traditional weaving. These jargons were distinguished into three type. Based on the process of producing kambeng songket, there were twelve jargons found. Related to the name of tools and ingredient, there were twenty-three jargons found. Lastly, there were six jargons concerned with naming the motif. All of the jargons have their own meaning used by the weavers in order to communicate each other. This research also helped to document the jargons that exist in Balinese traditional weaving community.